Results from Bottom Trawl Survey on Flemish Cap of June-July 2007 - Vázquez, Antonio; González-Troncoso, Diana (Northwest Atlantic Fisheries Organization, 2008)
A stratified random bottom trawl survey on Flemish Cap was carried out on June - July 2007, covering the bank up to 1460 m depth (800 fathoms). The survey was carried out on board R/V Vizconde de Eza, using a Lofoten bottom trawl gear, and 174 haul were done, 117 of them in the region with less than 730 m depth. Survey results are presented and compared with results of previous surveys in the series since 1988. Biomass and abundance indices are provided for main commercial species, as well as age composition for cod, American plaice, and Greenland halibut.